Penerapan Edukasi SDGS di Lingkungan Sekolah Guna Mendukung Terwujudnya Kesejahteraan Pendidikan - Lestari, Binita Bhekti; Nugraheni, Nursiwi; Husain A, Fajar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Sustainable development is simply development that meets the needs of the present without reducing the needs of future generations.The method used in this research is library research by taking references from various websites and international journals where the basis for the discussion is from the results of literature studies through several sources of scientific articles and from relevant journals from previous research results that are in accordance with the topic of discussion. The writing in this research explains the importance of education from an early age in the school environment in supporting the realization of educational prosperity in Indonesia, which is a developing country that is still ranked 57th out of 115 countries in 2015. The aim of conducting Sustainable Development Goals (SDGS) research This is to give students an idea of how important Sustainable Development Goals (SDGS) education is from an early age to support the realization of educational prosperity in Indonesia, which can still be said to be of low quality. Then look at the current condition of education and the role of the government and other parties such as private educational institutions in overcoming the low level of education to improve the quality of education in Indonesia. It is hoped that the SDGs program can overcome the problem of education which is still unequal and can improve its quality in order to make the Indonesian nation more advanced.